INTEGRATED INITIAL WATER SATURATION MODELLING - Falza Izza Wihdany; Dedy Irawan; Muhammad Rakha Utomo; Agung Mubaroqan Fitro (Testing Center for Oil and Gas LEMIGAS, 2019)
This study presents a new approach to estimate initial water saturation. The initial water saturation is determined by integrating formation tester (RFT), drill stem test (DST), well logging, and laboratory measurement (RCAL & SCAL) data. This method utilizes Brook-Correy’s parametrical equation to determine synthetic capillary pressure and initial water saturation as a function of depth and rock type. Rock type and permeability are distributed vertically by using well log interpretation. DST and formation tester data are used to control the initial water saturation calculation. The calculation needs to iterate Brook-Correy’s constant by using solver until the results are matching with all data. The precise step of this method is presented by using synthetic data (ideal reservoir characteristic). Case studies are provided for testing the proposed method. The product of this study is essential where well log data could be changed by time (production activity) and core measurement data are very limited. The results of case studies demonstrate that the method is not affected by rock mineralogy or reservoir condition. This new approach is successfully integrated and matched with field and laboratory measurement data. Moreover, the method could be applied in any reservoir.